Система обліку персональних витрат - Михальчук, М. О. (ХНУРЕ, 2023)
Over the past decade, cost accounting systems have become increasingly popular. They act as personal financial assistants: they provide a detailed report on income and expenses, help you stick to a monthly spending plan, and remind you about regular payments. This article examines the shortcomings of existing software tools, the advantages and disadvantages of popular OCR systems and text recognition methods. A method of improving accounting systems using OCR technology is proposed.